Transformative Research and Higher Education - Bacal, Azril, 1941- (Emerald Publishing Limited, 2022)
Providing a critical look at how it is possible for institutions of higher education to go beyond the institutional constraints that plague the neo-liberal university, the authors of this volume explore the powerful role of transformative university-based research and education.